2011
DOI: 10.1590/1808-1657v78p2252011
|View full text |Cite
|
Sign up to set email alerts
|

Levantamento E Flutuação Populacional De Parasitoides De Moscasdas-Frutas (Diptera: Tephritidae) De Ocorrência Em Goiabeira (Psidium Guajava L.) Em Fortaleza, Ceará

Abstract: RESUMO Objetivou-se com o presente trabalho conhecer os himenópteros parasitoides associados às moscas-das-frutas (Diptera: Tephritidae) de ocorrência em pomar urbano de goiabeira (Psidium guajava L.) (Myrtaceae), em Fortaleza, Ceará, bem como determinar a flutuação populacional desses organismos nesse ecossistema. Realizaram-se coletas de frutos maduros em plantas de goiabeira e frutos recém-caídos, no período de novembro de 1999 a outubro de 2000. Os parasitoides obtidos pertencem às famílias Braconidae, Cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 8 publications
0
0
1
Order By: Relevance
“…The average infestation rate/kg was higher than those reported by other studies such as the survey carried out by Santos et al (2012), in which they found infestation of 99.3 puparium/kg in collections carried out in organic guava crops in the municipality of Maceió, Alagoas. Similarly, Moura & Moura (2011) found infestation levels lower than the findings of the present study, reporting 30.3 puparium/kg in samples collected in a guava orchard in Fortaleza, Ceará.…”
Section: Resultscontrasting
confidence: 66%
“…The average infestation rate/kg was higher than those reported by other studies such as the survey carried out by Santos et al (2012), in which they found infestation of 99.3 puparium/kg in collections carried out in organic guava crops in the municipality of Maceió, Alagoas. Similarly, Moura & Moura (2011) found infestation levels lower than the findings of the present study, reporting 30.3 puparium/kg in samples collected in a guava orchard in Fortaleza, Ceará.…”
Section: Resultscontrasting
confidence: 66%